ANALISIS PENINGKATAN JUMLAH CALON JEMAAH UMRAH MELALUI BAURAN PROMOSI DI PT. AL SHAFWAH WISATA MANDIRI SMARTS UMRAH CAB.AGAM - Nurul Azizah; Zulhelmi (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
The promotional mix is the total marketing communications program of a company consisting of advertising, sales promotion, public relations, publication and direct marketing which is used by the company to achieve advertising and marketing objectives in increasing sales targets.The purpose of this research is to determine efforts to increase the number of prospective pilgrims through promotional mix strategies at PT Al Shafwah Wisata Mandiri Smarts Umrah Cab. Agam. This type of research is field research, which takes data directly from the research site. The data sources used are primary data obtained from interviews and observations, and secondary data obtained from documents regarding the research object. The informants from this research were Travel Leaders, Congregation Mentors and employees. The results of research conducted at PT Al Shafwah Wisata Mandiri Smarts Umrah Cab. Agam in an effort to increase the number of prospective Umrah pilgrims through a promotional mix through, advertising which is carried out in the form of online and offline, namely, tik-tok, Instagram, Whatsapp, and offline such as brochures, banners. Sales Promotions that are carried out provide discounts or discounts. Public relations is carried out by establishing relationships with external parties. Personal Selling is carried out by directly contacting or making offers to suspected people. Direct Marketing is carried out by coming directly to homes and also at religious studies